THE REGIME OF MODEM WATER-GRAVITY AND MUDFLOWS PROCESSES IN SVALYAVSKY AND VOLOVETSKY DISTRICTS OF ZAKARPATSKY REGION - IVANIK, O.; LISOVA, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The dangerous geological processes that have been observed in June of 2006 in Svalyavsky and Volovetsky districts of Zakarpatsky region were considered. The analysis of their appearance factors was realized. The morphological and morphometrical peculiarities of landslide bodies were determined.